High‐density linkage map construction and QTL analysis of fiber quality and lint percentage in tetraploid cotton. Issue 5 (2nd July 2021) - Zhu, Linglong; Andres, Ryan J.; Zhang, Kuang; Kuraparthy, Vasu
Abstract: Improving fiber quality and yield are major research objectives for cotton breeders in the United States. Identifying broadly existing and stable quantitative trait loci (QTLs) related to fiber quality is critical to properly utilizing genomic resources in cotton improvement programs. An F6 recombinant inbred line (RIL) population derived from the cross of NC05AZ21 × TX‐2324 was used to develop linkage maps and for QTL analysis of six fiber quality traits and lint percentage. The Illumina 63K single nucleotide polymorphism (SNP) array was used to genotype the RIL population. Analysis of variance of phenotypic trait data showed significant differences among lines and years for all traits tested. The heritability for tested traits ranged from 0.56 to 0.91. Genetic mapping was performed using 3, 009 polymorphic SNP markers on the RILs. We constructed a genetic map with a total length of 4, 983.73 cM and an average distance of 1.66 cM between markers. The linkage map corresponded well with the Upland cotton ( Gossypium hirsutum L.) sequence‐based physical map. Thirty‐two QTLs with additive effects for lint percentage and fiber quality traits were identified on 15 chromosomes, explaining 7.9–22.2% of the phenotypic variance. The majority of these QTLs were mapped in the D subgenome, indicating that functional mutations in the D subgenome are responsible for the major fiber quality improvements in Upland cotton. Furthermore, five QTL clusters were located on four chromosomes (Chr.05, Chr.18, Chr.19, and Chr.26), which may explain the strong correlation between fiber quality traits measured. The QTLs identified in the current study could be targeted for marker‐assisted selection and map‐based cloning of fiber quality traits in Upland cotton. Core Ideas: QTL mapping using a SNP array on a recombinant inbred line population was performed. The genetic map of SNPs corresponded well with the sequence‐based physical map. Thirty‐two QTLs for six fiber quality traits and lint percentage were identified. The D subgenome harbored the majority of QTLs for fiber quality in Upland cotton. QTLs for fiber quality traits clustered on a handful of chromosomal regions.